THE IMPACT OF FITNESS ACTIVITY ON THE MORPHOLOGICAL CHARACTERISTICS OF FEMALES - Milena Mikalački; Nebojša Čokorilo (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Body building is reserved for male population. It is interesting because we are concerned with the effect of experimental treatment on muscles and fats. Fat volume is indirect relationship with obesity. Obesity is a disease which is more common among female population than the male one. In order to treat a person as an obese one, he/she must have extra fat, i.e. above that which is treated as normal for a particular age. One of the reasons for which fat is bad is that it lowers muscle power, flexibility and cardiovascular endurance. "Male sexual hormone (testosterone) increases basal metabolism more (even by 30 %) than the female one. Basal metabolism is actually lower in females as they have higher percentage of fat tissue than the male ones. When the body mass is treated as a value without the fat tissue, this difference disappears". (Nikolić, 1995). Women may freely exercise under load and consume their fat tissue.